2016
DOI: 10.1007/s13277-015-4776-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of three different chemotherapy regimens delivered with concomitant radiotherapy in inoperable stage III non-small cell lung cancer patients

Abstract: Concomitant administration of chemotherapy and radiotherapy is currently recognized as the standard of treatment in locally advanced inoperable non-small cell lung cancer (NSCLC). Our study aimed to compare the efficacy and toxicities of three different chemotherapy regimens delivered concurrently with radiotherapy. We retrospectively reviewed the clinical records of patients who received the PE (cisplatin, 50 mg/m(2), on days 1, 8, 29, and 36 plus etoposide, 50 mg/m(2), on days 1 to 5 and 29 to 33), PD (docet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…As expected, and consistent with recent studies, 78,100 patients with CIN were more likely to have received a combination of a platinum and a taxane compound and had received higher cumulative doses of CTX. This finding may be related to the receipt of two different classes of CTX drugs that have both overlapping (e.g., mitochondrial dysfunction) and differential (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, and consistent with recent studies, 78,100 patients with CIN were more likely to have received a combination of a platinum and a taxane compound and had received higher cumulative doses of CTX. This finding may be related to the receipt of two different classes of CTX drugs that have both overlapping (e.g., mitochondrial dysfunction) and differential (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…With such a heterogeneous population, a multi-modality approach involving surgery, radiation, and systemic agents is most commonly employed. A standard treatment option for unresectable or inoperable stage IIIA and stage IIIB disease is concurrent chemoradiation, while management of IIIA is more complex and controversial[ 5 ]. Treatment options for IIIA disease includes surgery with neoadjuvant or adjuvant chemotherapy, radiation, or both; as well as definitive chemoradiation[ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A standard treatment option for unresectable or inoperable stage IIIA and stage IIIB disease is concurrent chemoradiation, while management of IIIA is more complex and controversial[ 5 ]. Treatment options for IIIA disease includes surgery with neoadjuvant or adjuvant chemotherapy, radiation, or both; as well as definitive chemoradiation[ 3 , 5 , 6 ]. Long-term outcomes are poor, with baseline 5-year overall survival (OS) of 15%-35% for stage IIIA and 5%-10% for stage IIIB[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that EP provided more favorable outcomes than DP. Ozcelik et al 27 compared the efficacy and toxicities of EP (etoposide, 50 mg/m 2 , on days 1 to 5 and 29 to 33 plus cisplatin, 50 mg/m 2 , on days 1, 8, 29, and 36), DP (docetaxel, 20 mg/m 2 , on day 1 plus cisplatin, 20 mg/m 2 , on day 1, every week), and PC (paclitaxel, 45 mg/m 2 , on day 1, every week plus carboplatin, AUC = 2) regimens delivered concurrently with radiotherapy for inoperable LA-NSCLC. Although the results did not prove a statistically significant difference in OS among the groups (37 months, 27 months and 23 months, respectively.…”
Section: Discussionmentioning
confidence: 99%